2005
DOI: 10.3748/wjg.v11.i8.1109
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adequate immunosuppressive therapy for the recovery of patients with “life-threatening” severe exacerbation of chronic hepatitis B

Abstract: The introduction of high-dose corticosteroid can reverse deterioration in patients with "clinically life-threatening" severe exacerbation of chronic hepatitis B, when used in the early stage of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
2
39
2
Order By: Relevance
“…Thus, ETV is considered a first-choice therapy for patients with chronic hepatitis B not previously treated with a nucleoside analogue. However, for patients with severe exacerbation of chronic hepatitis B, treatment during the first 2 wk determines their prognosis [9] . The liver cell injury caused by HBV infection is mediated mainly by the response of CD8+ cytotoxic T lymphocytes to small epitopes of HBV proteins, especially the hepatitis B core antigen, present on the surface of liver cells [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ETV is considered a first-choice therapy for patients with chronic hepatitis B not previously treated with a nucleoside analogue. However, for patients with severe exacerbation of chronic hepatitis B, treatment during the first 2 wk determines their prognosis [9] . The liver cell injury caused by HBV infection is mediated mainly by the response of CD8+ cytotoxic T lymphocytes to small epitopes of HBV proteins, especially the hepatitis B core antigen, present on the surface of liver cells [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, viral resistance, which is usually followed by a loss of clinical response, a rise in aminotransferase levels and worsening of hepatic histology, is related to mutations in the tyrosinemethionine-aspartate-aspartate (YMDD) motif which occurs in 70%-80% of patients treated continuously for 4-5 years [8] . Recently, the early introduction of highdose corticosteroid was reported to improve the shortterm prognosis of patients with severe exacerbation of chronic hepatitis B [9] . In this report, we describe 2 cases with severe exacerbation of chronic hepatitis B successfully treated with a combination of entecavir (ETV) and corticosteroid.…”
Section: Introductionmentioning
confidence: 99%
“…35 Previous studies suggest that the use of corticosteroids was crucial for preventing liver cell necrosis when used in the early stage of severe hepatitis. 19 Given this, we speculated that the potential direct effect of glucocorticoids on certain inflammatory regulators could be evaluated for better therapeutic efficacy. Previous studies revealed that overwhelming pro-inflammatory cytokines were secreted after the activation of mononuclear macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 As an optional therapy for ACHBLF, corticosteroid treatment has received much attention. [18][19][20][21] Glucocorticoids suppresses inflammation by controlling and preventing the immune-correlated damages. The upregulation of SOCS1 by corticosteroids has been established both in vivo and in vitro, [22][23][24] which suggests that cortisol may be playing a key role in suppressing cytokine signaling and the associated inflammatory response through SOCS1.…”
mentioning
confidence: 99%
“…7 The increase in hepatitis B viral replication also has been shown to occur in patients taking chemotherapy 9,10 and corticosteroids. 11,12 However, acute pancreatitis that was developed in healthy HBV carriers with spontaneous acute exacerbation of chronic HBV infection is rare.…”
Section: Discussionmentioning
confidence: 99%